The American way of life : a cultural history - Samuel, Lawrence R. (Fairleigh Dickinson University Press series in American history and culture, 2017)
The American Way of Life is a cultural history of the American Way of Life (or more simply the American Way). The book argues that since the term was popularized in the 1930s, the American Way has served as the primary guiding mythology or national ethos of the United States.